Advanced glycation end-products induce skeletal muscle atrophy and dysfunction in diabetic mice via a RAGE-mediated, AMPK-down-regulated, Akt pathway - Chiu, Chen-Yuan; Yang, Rong-Sen; Sheu, Meei-Ling; Chan, Ding-Cheng; Yang, Ting-Hua; Tsai, Keh-Sung; Chiang, Chih-Kang; Liu, Shing-Hwa (The Journal of pathology, 2016)
Diabetic myopathy, a less studied complication of diabetes, exhibits the clinical observations characterized by a less muscle mass, muscle weakness and a reduced physical functional capacity. Accumulation of advanced glycation end‐products (AGEs), known to play a role in diabetic complications, has been identified in ageing human skeletal muscles. However, the role of AGEs in diabetic myopathy remains unclear. Here, we investigated the effects of AGEs on myogenic differentiation and muscle atrophy in vivo and in vitro. We also evaluated the therapeutic potential of alagebrium chloride (Ala‐Cl), an inhibitor of AGEs. Muscle fibre atrophy and immunoreactivity for AGEs, Atrogin‐1 (a muscle atrophy marker) and phosphorylated AMP‐activated protein kinase (AMPK) expressions were markedly increased in human skeletal muscles from patients with diabetes as compared with control subjects. Moreover, in diabetic mice we found increased blood AGEs, less muscle mass, lower muscular endurance, atrophic muscle size and poor regenerative capacity, and increased levels of muscle AGE and receptor for AGE (RAGE), Atrogin‐1 and phosphorylated AMPK, which could be significantly ameliorated by Ala‐Cl. Furthermore, in vitro, AGEs (in a dose‐dependent manner) reduced myotube diameters (myotube atrophy) and induced Atrogin‐1 protein expression in myotubes differentiated from both mouse myoblasts and primary human skeletal muscle‐derived progenitor cells. AGEs exerted a negative regulation of myogenesis of mouse and human myoblasts. Ala‐Cl significantly inhibited the effects of AGEs on myotube atrophy and myogenesis. We further demonstrated that AGEs induced muscle atrophy/myogenesis impairment via a RAGE‐mediated AMPK‐down‐regulation of the Akt signalling pathway. Our findings support that AGEs play an important role in diabetic myopathy, and that an inhibitor of AGEs may offer a therapeutic strategy for managing the dysfunction of muscle due to diabetes or ageing. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.